PEMANFAATAN DAN STRATEGI INSTAGRAM DALAM MENINGKATKAN BRAND AWARENESS - Setya, Irwan; Ananda, Dava Putra; Umam, Akhmad Hairul (Sintesa, 2024)
Teguk Indonesia is a local brand that sells contemporary beverage products currently trending among young people. As a new entrant facing many competitors, this company certainly needs to increase its brand awareness to attract many consumers. This research aims to determine the marketing communication strategy and brand awareness of Teguk Indonesia through its Instagram using a descriptive qualitative approach. Teguk Indonesia's marketing communications strategy focuses on creating content that can attract the target market's attention. This content is designed to attract attention and arouse interest by displaying various unique and contemporary drink flavours, thus triggering a desire to try the product. These efforts are complemented by clear calls to action, such as special promotions, invitations to visit a store, or participation in a giveaway to encourage purchasing action. Through analysis of interactions on social media, this study identified that Teguk Indonesia has also succeeded in building brand equity, which can be seen from the high level of brand recognition, perceived quality and customer loyalty. Active interaction between brands and consumers through comments and DM (Direct Message) and the use of influencers and posts shows the practical application of brand equity theory ten. This research reveals that by utilizing Instagram, Teguk Indonesia not only increases brand awareness among its target audience but also maintains long-term relationships with consumers. This shows the importance of a digital marketing communications strategy integrated and responsive to market dynamics and consumer preferences. This success provides essential findings for other brands in similar industries to optimize their social media presence to increase brand awareness and customer loyalty. Keywords: Marketing Communcation, Instagram, AIDA, Brand Awareness, Brand Equity.